2007
DOI: 10.2134/jeq2006.0371
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Plant Families in a Greenhouse Phytoremediation Study on an Aged Polycyclic Aromatic Hydrocarbon–Contaminated Soil

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous, recalcitrant, and potentially carcinogenic pollutants. Plants and their associated rhizosphere microbes can promote PAH dissipation, off ering an economic and ecologically attractive remediation technique. Th is study focused on the eff ects of diff erent types of vegetation on PAH removal and on the interaction between the plants and their associated microorganisms. Aged PAH-polluted soil with a total PAH level of 753 mg kg −1 soil dry weight was planted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 28 publications
2
36
2
Order By: Relevance
“…In this study, mass balance calculation showed that the amount of PAHs directly accumulated in plants took only 0.2-1.0 % of the dissipation enhancement for phenanthrene and 0.4-6.9 % for pyrene ( Table 2), suggesting that plant uptake was weak and plant-promoted biodegradation was the dominant contribution. Our results concurred with the findings of terrestrial plants and emergent aquatic plants (Sarand et al 1998;Hojae et al 2000;Singer et al 2003;Johnsena et al 2005;Olson et al 2007). …”
Section: Dissipation Of Pahs In Sedimentssupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, mass balance calculation showed that the amount of PAHs directly accumulated in plants took only 0.2-1.0 % of the dissipation enhancement for phenanthrene and 0.4-6.9 % for pyrene ( Table 2), suggesting that plant uptake was weak and plant-promoted biodegradation was the dominant contribution. Our results concurred with the findings of terrestrial plants and emergent aquatic plants (Sarand et al 1998;Hojae et al 2000;Singer et al 2003;Johnsena et al 2005;Olson et al 2007). …”
Section: Dissipation Of Pahs In Sedimentssupporting
confidence: 93%
“…Plant species differ in their root exudate composition (Singer et al 2003). As the root density increased, this may have led to a supraoptimal level of a certain root released compounds, inhibiting the rate of microbial PAH degradation and the number of PAH-degrading bacteria (Olson et al 2007). Potentials of four species of submerged aquatic plants remediating PAHs-contaminated sediments were examined in this study.…”
Section: Pah-degrading Bacterial Population In Sedimentsmentioning
confidence: 99%
“…Field-contaminated soils that have undergone prolonged periods of ageing (e.g. Phillips et al 2006;Ryslava et al 2003;Liste and Prutz 2006;Liste and Felgentreu 2006;Olson et al 2007;Muratova et al 2003;Demnerova et al 2005) generally appear to be much less responsive to rhizodegradation than freshly spiked soil (e.g. Dams et al 2007;Kaimi et al 2007;Lin et al 2006;Chiapusio et al 2007;Kim et al 2006;He et al 2005He et al , 2007Gunderson et al 2007;Child et al 2007).…”
Section: Rhizodegradationmentioning
confidence: 99%
“…Penetrating and breaking-up the soil, plant roots create the macropores that provide microorganisms by air and water resources thereby increasing microbial activities and biodegradation rates of pollutants. The accelerated degradation of organic pollutants by microorganisms in the planted soils in comparison with unplanted ones has been demonstrated (Huang et al 2005;Juhanson et al 2007;Olson et al 2007).…”
Section: Phytoremediation Of Polluted Soilsmentioning
confidence: 97%